Regulation and Physiological Significance of the Nuclear Shape in Plants - Goto, Chieko; Hara-Nishimura, Ikuko; Tamura, Kentaro (Frontiers in Plant Science, 2021)
The shape of plant nuclei varies among different species, tissues, and cell types. In Arabidopsis thaliana seedlings, nuclei in meristems and guard cells are nearly spherical, whereas those of epidermal cells in differentiated tissues are elongated spindle-shaped. The vegetative nuclei in pollen grains are irregularly shaped in angiosperms. In the past few decades, it has been revealed that several nuclear envelope (NE) proteins play the main role in the regulation of the nuclear shape in plants. Some plant NE proteins that regulate nuclear shape are also involved in nuclear or cellular functions, such as nuclear migration, maintenance of chromatin structure, gene expression, calcium and reactive oxygen species signaling, plant growth, reproduction, and plant immunity. The shape of the nucleus has been assessed both by labelling internal components (for instance chromatin) and by labelling membranes including the NE or endoplasmic reticulum in interphase cells and viral-infected cells of plants. Changes in NE are correlated with the formation of invaginations of the NE, collectively called the nucleoplasmic reticulum. In this review, what is known and what is unknown about nuclear shape determination are presented, and the physiological significance of the control of the nuclear shape in plants is discussed.